Determinants of financial reporting quality moderated by compensation: evidence from Nagari-owned enterprises - Olivia, Hastuti; Muliadi, Selamat; Ginanjar, Yogi; Kuraesin, Arlis Dewi; Yanti, Evi Maulida (LPPM ISNJ Bengkalis, 2025)
Purpose – This research analyses the influence of accounting application technology, work experience, and educational background on financial report quality moderated by compensation. Method – This research used a causally associative approach and a quantitative method. Employees of Nagari-owned enterprises (BUMNag) in West Sumatera province were included in this research. Purposive sampling was used to choose the 99 employees that made up the research sample. Data was analyzed using partial least squares-structural equation modelling (PLS-SEM) with SmartPLS. Findings – The results indicate that accounting application technology, work experience, and educational background positively affect the quality of financial reports. However, compensation does not affect the quality of BUMNag's financial reports in West Sumatera province. Compensation can strengthen the effect of accounting application technology and work experience on quality financial reports. However, it cannot moderate the relationship between education background and financial report quality. Implications – Theoretically, this study can enrich the literature on factors that influence the quality of financial reports, especially in the context of public sector organizations such as BUMNag. Practically, it can improve the quality of financial reports by developing policies related to the use of accounting technology and improving HR competencies through training and recruitment based on educational background and work experience.